(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research survey was an attempt to present the process of study about “Difficulties in speaking of English majored freshmen at Tay Do University”. The participants of the research were 36 English majored freshmen from Bachelor of English at Tay Do University. The instruments of this study were questionnaires, paper interview questions, and the observation sheet. English-majored freshmen just begin to learn speaking English skill. Thus, they would get many challenges in speaking English. The results of this research would highlight the difficulties in speaking English that English majored freshmen faced. The goal was to identify problems, facilitate solutions, and to assist teachers and students to overcome these difficulties together.